IDENTIFICATION OF BAWANG SABRANG (Eleutherine americana Merr. ex K. Heyne) IN INDONESIA BASED ON CHROMOSOME CHARACTERS - Daryono, Budi Setiadi; Rahmadani, Wenny Deisshinta; ., Sudarsono (Indonesian Journal of Pharmacy, 2013)
Bawang Sabrang (Eleutherine americana Merr. ex K. Heyne) is a plant belongs to Iris family (Iridaceae). Genetic study of the Eleutherine species should be investigated to yield valuable information for breeding program. The aim of this research was to determine chromosome characters as a preliminary research on the genetic characterization of Bawang Sabrang. Squash method on the root tips was used for chromosome preparation of this plant. The results showed that the time of cell division and prometaphase stages of Bawang Sabrang were occurred at about 08.00-08.30 a.m. and 08.20 a.m., respectively. Chromosome number of Bawang Sabrang was 2n=12 and the karyotype consisted of 8 (4 pairs) of metacentric chromosomes, 2 (1 pair) submetacentric chromosomes and 2 (1 pair) subtelocentric chromosomes which have the longest of total length chromosomes. Therefore, the karyotype formula of Bawang Sabrang was 2n=12=8m+2sm+2stSAT. Besides that, on the pair of subtelocentric chromosomes there was a satellite at each of the chromosome. Analysis of chromosome characters exhibited that the long of total length chromosomes was about 1.687 ± 0.111 µm to 5.320 ± 0.716 µm. Based on the R value ( 3,65 ± 0,41), it revealed that there was variation of chromosome size on this Eleutherine species in Indonesia. Moreover, data of the chromosome characters is important to complete the database of Bawang Sabrang as a potential medicinal herb in Indonesia Keywords: Bawang Sabrang, Eleutherine americana, chromosome, karyotype